Industry Characteristics, Risk Premiums, and Debt Pricing - Amiram, Dan; Kalay, Alon; Sadka, Gil (The Accounting Review, 2017)
ABSTRACT Despite theoretical and anecdotal evidence highlighting the importance of industry-level analyses to lenders, the empirical literature on debt pricing has focused almost exclusively on firm-level forces that affect expected loss. This paper provides empirical evidence that industry-level characteristics relate to debt pricing through risk premiums. We address the empirical challenges that arise when testing these theories by using a proprietary dataset of time-varying and forward-looking measures of industry characteristics. These characteristics include growth, sensitivity to external shocks, and industry structure, all measured at the six-digit NAICS level. Our results show that lenders demand higher spreads to bear industry-level risk. The relation exists within subsamples with constant credit ratings, and strengthens when lenders' loan portfolios are less diversified and during periods when diversification is difficult. Therefore, our results suggest that industry characteristics relate to debt pricing by informing lenders not only about expected loss, but also about risk premiums. JEL Classifications: G31; G32; G33; M21.